Policies and Prospects in Japan and the Implications for the Asia-Pacific Region - Callen, Tim (IMF Working Papers; Working Paper ;, 2001)
This paper uses the G-Cubed (Asia-Pacific) model-a macroeconomic model with rich cross-country links-to explore the implications for Japan and Asia of several shocks to the Japanese economy. The results suggest that, while fiscal consolidation in Japan would initially dampen domestic growth, over the medium term the impact on both the domestic and regional economies would be positive. Quantitative monetary easing in Japan would boost domestic activity in the short-run, while being basically neutral for the region. Finally, a loss of confidence in the yen would be negative for Japan, but positive for the region because of a reallocation of capital flows toward non-Japan Asia.